2017
DOI: 10.1136/bmjopen-2016-013502
|View full text |Cite
|
Sign up to set email alerts
|

Are patients with cancer with sepsis and bacteraemia at a higher risk of mortality? A retrospective chart review of patients presenting to a tertiary care centre in Lebanon

Abstract: ObjectiveMost sepsis studies have looked at the general population. The aim of this study is to report on the characteristics, treatment and hospital mortality of patients with cancer diagnosed with sepsis or septic shock.SettingA single-centre retrospective study at a tertiary care centre looking at patients with cancer who presented to our tertiary hospital with sepsis, septic shock or bacteraemia between 2010 and 2015.Participants176 patients with cancer were compared with 176 cancer-free controls.Primary a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
47
2
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 27 publications
(38 reference statements)
5
47
2
4
Order By: Relevance
“…These were compared to another 176 non-oncological patients coming from the same database. Although the hospital mortality of the oncological patients was significantly greater than the non-oncological patients, their severity as defined by their vital signs and requirement for vasopressors was also significantly greater than the non-oncological patients [15]. The second study is a retrospective analysis of the REGARDS database.…”
Section: Discussionmentioning
confidence: 99%
“…These were compared to another 176 non-oncological patients coming from the same database. Although the hospital mortality of the oncological patients was significantly greater than the non-oncological patients, their severity as defined by their vital signs and requirement for vasopressors was also significantly greater than the non-oncological patients [15]. The second study is a retrospective analysis of the REGARDS database.…”
Section: Discussionmentioning
confidence: 99%
“…Abou et al (Dagher et al, 2017) estudiaron, 352 pacientes, 176 con cáncer se compararon con 176 sin cáncer, los resultados, describen, que el nivel sérico de lactato, a la presentación en emergencia de los pacientes con cáncer fue de 4mg/dl, 44 % del grupo de cáncer vs 26 % del grupo control. En otros estudios, el nivel de lactato en pacientes con cáncer e infección se ha tomado con un corte de 2,98mmol/L, pero este valor ha tenido poco valor discriminativo (Keçe et al, 2016).…”
Section: Rol Del Lactato En Al Paciente Oncológico Con Sepsisunclassified
“…En el año 2010 Mato et al (Dagher et al, 2017), encontraron que, en pacientes con neutropenia febril, quienes no presentaban inestabilidad cardiovascular, una elevación de lactato ¿2mmol/L, dentro de las 26 horas iniciales, de seguimiento de la neutropenia febril, podría predecir, infección con riesgo elevado de inestabilidad cardiovascular y choque.…”
Section: Rol Del Lactato En Al Paciente Oncológico Con Sepsisunclassified
“…Another association study revealed 2.5 fold increased risk of sepsis in survivors of cancer in community-dwelling adults (the risk is increased up to 10 times in hospitalized cancer patients) [3]. Co-occurrence of cancer with sepsis is associated with higher mortality than sepsis alone without cancer [4]. On the other hand, sepsis is a common cause of death in critically ill patients with cancer, with high ICU and hospital mortality [5][6][7].…”
Section: Introductionmentioning
confidence: 99%